Design And Build Of A Cafe Dashboard Application As Information System Of Sales Performance PT. Maxx Coffee Prima - Audrey Arianto, Putri; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Journal of Engineering, Technology and Computing (JETCom), 2023)
PT.Max Coffe Prima is one of the companies that engaged in the sale of food and beverages. At this company all sales reporting proces are still carried out using group chat which of course is considered very ineffective and efficient and causes many problems, one of which is a problem with storing report data. Report data does not have a back up so it is easy to sink or disappear from group chats. And to overcome these problems and facilitate the process of reporting sales and giving rewards to sales, a study was made entitled Design And Build Of A Café Dashboard Application As Information System Of Sales Performance PT. Maxx Coffee Prima. By using the Unifield Modeling Language (UML) as the modeling and MySQL as the database and PHP as the programming language.